Why companies should help every employee chart a career path : providing career development to all employees requires a commitment to clarifying pathways for growth and giving everyone opportunities to build new skills - Westerman, George, 1963-; Lundberg, Abbie (MIT Sloan Management Review, 2023)
When it comes to providing career development support for employees, most companies offer three key elements — visibility into opportunities and paths, the means to learn and practice, and rich feedback and coaching — only to high-potential performers. The authors explain how organizations can integrate those elements into a career development system that works across all levels of the workforce to boost retention and cultivate needed skills.